The Gender Cliff in the Relative Contribution to the Household Income: Insights from Modelling Marriage Markets in 27 European Countries - André Grow; Jan Van Bavel (European Journal of Population, 2020)
In Western countries, the distribution of relative incomes within marriages tends to be skewed in a remarkable way. Husbands usually do not only earn more than their female partners, but there is also a striking discontinuity in their relative contributions to the household income at the 50/50 point: many wives contribute just a bit less than or as much as their husbands, but few contribute more. This `cliff' has been interpreted as evidence that men and women avoid situations where a wife would earn more than her husband, since this would go against traditional gender norms. In this paper, we use a simulation approach to model marriage markets and demonstrate that a cliff in the relative income distribution can also emerge without such avoidance. We feed our simulations with income data from 27 European countries. Results show that a cliff can emerge from inequalities in men's and women's average incomes, even if they do not attach special meaning to a situation in which a wife earns more than her husband.
Keywords: 300; Marriage markets; Income; Gender norms; Gender inequality; Simulation modelling